The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1152/ajplung.00159.2015
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus infection increases chlorine-induced airway hyperresponsiveness

Abstract: -Exposure to chlorine (Cl2) damages airway and alveolar epithelia resulting in acute lung injury and reactive airway hyperresponsiveness (AHR) to methacholine. However, little is known about the effect of preexisting respiratory disease on Cl2-induced lung injury. By using a murine respiratory syncytial virus (RSV) infection model, we found that preexisting RSV infection increases Cl2 (187 ppm for 30 min)-induced lung inflammation and airway AHR at 24 h after exposure (5 days after infection). RSV infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…The current clinical definition of BPD relies exclusively on the need for – and degree of – oxygen supplementation in affected neonates; however, lung structure plays no role in this definition. In contrast, no studies on respiratory function or lung mechanics 191 , which include parameters central to current diagnostic criteria for BPD, are currently performed in animal models of BPD, largely due to technical challenges associated with adapting available technology to very small animals. Studies on the relationship of lung structure to function in experimental animals are essential, similar to a recent study that examined this relationship in oxygen-injured developing lungs 192 .…”
Section: Understanding Bpd Pathobiology – Future Directionsmentioning
confidence: 99%
“…The current clinical definition of BPD relies exclusively on the need for – and degree of – oxygen supplementation in affected neonates; however, lung structure plays no role in this definition. In contrast, no studies on respiratory function or lung mechanics 191 , which include parameters central to current diagnostic criteria for BPD, are currently performed in animal models of BPD, largely due to technical challenges associated with adapting available technology to very small animals. Studies on the relationship of lung structure to function in experimental animals are essential, similar to a recent study that examined this relationship in oxygen-injured developing lungs 192 .…”
Section: Understanding Bpd Pathobiology – Future Directionsmentioning
confidence: 99%
“…However, an important role for ECM is emerging. Exposure to ozone or cigarette smoke and asthma induce the release of sHA (4,15,16), which activates the TLR4 pathway, leading to airway inflammation (17)(18)(19) and hyperresponsiveness (AHR) (15,(17)(18)(19)(20). Importantly, I␣I is necessary for the development of ozone-induced AHR (15), as well as after other short-acting oxidative injury, like chlorine gas exposure (17).…”
mentioning
confidence: 99%
“…(17) Some researchers have shown that the mechanism underlying airway hyper-responsiveness caused by RSV infection is different from that caused by bronchial asthma. (18,19) Our previous studies had confirmed that M. vaccae nebulization can reduce the airway hyperresponsiveness and inflammation in the asthmatic model of mice. (7) This study demonstrated that M. vaccae nebulization reduced neither the airway hyper-responsiveness nor the airway inflammation caused by the RSV infection.…”
Section: Discussionmentioning
confidence: 84%